AIR MATA PENGANTIN: KEARIFAN BUDAYA RIAU DALAM TANAMAN DAN MINUMAN TRADISIONAL - Annisa Mutia; Syakirah Permata Auliya; Ginna Arvi Nanda; Syafira Atika Putri; Naila Awalia; Antoni Antoni; Yohannes Paulus Sinaga; Rado Justeza; Iqbal Ibrahim (CV. Denasya Smart Publisher, 2025)
Air mata pengantin is a term used to refer to both the plant Antigonon leptopus and a traditional beverage of the Malay Riau community. This study aims to examine the botanical aspects of A. leptopus and the cultural significance of the es air mata pengantin beverage within the Malay Riau society. A. leptopus is a climbing plant from the Polygonaceae family, characterized by clusters of pink to white flowers, and is rich in bioactive compounds such as flavonoids, polyphenols, alkaloids, saponins, and tannins, which have potential antioxidant and anti-inflammatory properties. Meanwhile, es air mata pengantin is a traditional beverage made from colorful agar, grass jelly, basil seeds, red syrup, and shaved ice, named as such due to its appearance resembling the beauty of A. leptopus flowers. The use of the same name for both the plant and the beverage reflects the local wisdom of the Malay Riau community in linking natural beauty with life values and cultural traditions. This phenomenon also indicates the process of cultural value transmission and the transformation of traditional culinary practices into regional cultural identity. Therefore, the preservation and further development of A. leptopus utilization as an ornamental plant and traditional medicinal plant are necessary to support the sustainability of local wisdom and Indonesia's biodiversity